Fertility Intentions for a Second Child and Their Influencing Factors in Contemporary China - Li, Mingming; Xu, Xinxin (Frontiers in Psychology, 2022)
Although the Chinese government has shifted from a one-child policy to a two-child policy (allowing a couple to have up to two children) since 2015 in response to the aging population, the policy results have been unsatisfactory. This is the first paper to systematically investigate the factors influencing residents’ intentions to have a second child. The research focuses on the perspective of individual, family, and social characteristics based on the Chinese General Social Survey (CGSS) from 2017 and 2018. Three machine learning methods—artificial neural network (ANN), random forest (RF), and XG-boost—are used in conjunction with logistic regression to reveal that the likelihood of having a second child increases with age, more siblings in the family of origin, and better health. This study also reveals differences between genders: Women with a higher level of education and lack of religious beliefs are less likely to have a second child, whereas for men, non-agricultural hukou and marriage are the factors that most influence the decision.